ARAB ETHNOPOLITICS, SPICE TRADE, AND ISLAM IN EASTERN INDONESIA - Deni, Aji; Kristanto, Budi (Department of Government, FISIP, Universitas Padjadjaran, 2026)
This study addresses the critical gap in understanding the ethnopolitical influence of Arab traders in shaping Eastern Indonesia. Specifically, it investigates the central research question: How did Arab traders leverage the spice trade and the spread of Islam to influence local political, social, and economic structures in Eastern Indonesia, and what explains the regional variation in this impact? Drawing on the theoretical lens of transregional trade networks and ethnopolitical entrepreneurship, the research employs a structured qualitative data analysis (QDA) of historical archives, and digital sources. The QDA focused on identifying and classifying patterns of influence, cultural exchange, and economic impact. The analysis revealed four key themes: the social and political influence of Arab traders (leading to the establishment of Islamic sultanates), the mitigating impact of European colonialism, the enduring economic influence of the spice trade, and the processes of cultural exchanges through Islam. The findings indicate that Arab traders were pivotal in Islamization and establishing early Islamic sultanates in key spice centers (Ternate, Tidore, Makassar). However, this influence was notably weaker in areas like Manado and Fak-Fak Papua due to competing indigenous and colonial factors. The study concludes that Arab ethnopolitics were a central force in the region's Islamization.